Assessment of Sparus aurata (Gilthead Seabream) stock in Bardawil lagoon, southeast Mediterranean Sea - Ahmed El-Aiq; Mohamed Raaft; El-Dakar A Youssef; Salem M Ahmed; Ahmed M Al-Beak; Kassem S Ahmed (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2021)
During present study period from October 2020 to April 2021, gilthead seabream Sparus aurata stock was estimated by using many assessment models to evaluate actual status on Bardawil lagoon. Length at first capture (Lc) was 17.10 and 16.70 cm for females and males respectively, but it was 16.9 cm for all individuals that corresponding age at first capture (tc= 2.49 year). Length at first recruit Lr was 10.70 and 9.70 cm for females and males, respectively, corresponding age tr= 0.77 year. The length at first maturity was Lm= 18.18 cm that corresponding age tm= 2.85 years. Virtual population analysis shows some of intensive capture on S. aurata at its early life's. Yield per recruit and biomass per recruit tend to collapse as a result of high fishing mortalities. The current study concludes an exact overfishing pressure of S. aurata stock in Bardawil lagoon.